Promoting Safety and Injury Prevention in Movement and Sport Environments - Cahyo Yuwono; Adi S; Tri Nurharsono; Dicky Budhi Setyawan; Supriyono Supriyono; Sri Indah Ihsani; Made Bang Redy Utama; Hilmy Aliriad (Universitas Negeri Semarang, 2025)
The high risk of injury in Physical Education activities in primary schools is an important issue that requires special attention, especially since most teachers do not have adequate training in dealing with emergencies such as physical injuries, heart attacks or other risky situations. This problem is reinforced by the lack of integration of safety protocols in learning and the absence of standardized safety policies in many schools. This community service activity aims to increase the capacity of Physical Education teachers through first aid and school safety training. The methods used include coordination with stakeholders, preparation of materials, pretest, theoretical and practical training, posttest, and evaluation of results. The training is delivered through lectures, demonstrations, case studies, and field simulations designed to match the real situation in the school environment. The results showed significant improvements in teachers' understanding of basic life support (100%), integration of classroom safety protocols (95%), and ability to handle student injuries (95%). The training also improved teachers' preparedness in using AEDs and implementing emergency evacuation procedures. In conclusion, systematic and contextualized training proved effective in improving the competence of PJOK teachers in safety and emergency response aspects. In the future, sustainable training programs and integrated school safety policies are needed to ensure a safe, inclusive and responsive learning environment to the risks that may occur during physical activities at school.